In Children, N -Methyl-D-Aspartate Receptor Antibody Encephalitis Incidence Exceeds That of Japanese Encephalitis in Vietnam - Huong, NHT; Toan, ND; Thien, TB; Khanh, TH; Tuan, NM; Truc, TT; Nghia, NA; Thinh, LQ; Thoa, NTK; Nhan, LNT; Minh, NNQ; Turner, HC; et al. (Oxford University Press, 2024)
Background: The recognition of autoimmune causes of encephalitis has led to epidemiological shifts in the worldwide characteristics of encephalitis. N-methyl-D-aspartate receptor (NMDAR) antibody encephalitis leads to well-established complex neuropsychiatric manifestations. In low- and middle-income countries, including Vietnam, its relative incidence, especially in children, is unknown and most neurologists currently consider infectious encephalitis prior to autoimmune etiologies. Methods: The study was prospectively conducted at Children's Hospital 1 in Ho Chi Minh City between March 2020 and December 2022. Any child admitted to the Department of Infectious Diseases and Neurology fulfilling the case definition of encephalitis was eligible to participate. Cerebrospinal fluid samples were collected alongside meta-clinical data for analysis. Results: We recruited 164 children with a clinical diagnosis of encephalitis. Etiologies were determined as NMDAR antibody encephalitis in 23 of 164 cases (14.0%), Japanese encephalitis virus in 14 of 164 (8.5%), and herpes simplex virus in 4 of 164 (2.4%). Clinical categorizations suggested idiopathic viral encephalitis in another 71 (43.3%), and autoimmune encephalitis of unknown origin in the remaining 52. Factors including demographics, specific clinical features, cerebrospinal fluid and electroencephalogram findings, and length of hospital stay were significantly different between NMDAR antibody encephalitis and Japanese encephalitis. Conclusions: At a tertiary children's hospital in Vietnam, the prevalence of NMDAR antibody encephalitis exceeds that of Japanese encephalitis, the most common infectious encephalitis cause in Southeast Asia. NMDAR antibody encephalitis is associated with long hospital stay and poor outcomes. These findings should change pediatric diagnostics, to earlier consider autoimmune treatments in this clinical setting.